2022
DOI: 10.1038/s41440-021-00806-y
|View full text |Cite
|
Sign up to set email alerts
|

Translational studies of adrenomedullin and related peptides regarding cardiovascular diseases

Abstract: Adrenomedullin (AM) is a vasodilative peptide with various physiological functions, including the maintenance of vascular tone and endothelial barrier function. AM levels are markedly increased during severe inflammation, such as that associated with sepsis; thus, AM is expected to be a useful clinical marker and therapeutic agent for inflammation. However, as the increase in AM levels in cardiovascular diseases (CVDs) is relatively low compared to that in infectious diseases, the value of AM as a marker of CV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(33 citation statements)
references
References 146 publications
0
33
0
Order By: Relevance
“…et al, are using different antibodies for the measurement of active AM, so our values tend to be lower than Simon, T.P. et al [108]. Moreover, similar results were obtained in patients with UC in a phase 2 trial, namely the concentration of AM reached 5.9 to 7.4 times the basal values; day 1: 67.4 ± 16.0 and day 8: 84.7 ± 48.1 pg/mL [115].…”
Section: Phase 2a Clinical Trial For Covid-19mentioning
confidence: 56%
See 2 more Smart Citations
“…et al, are using different antibodies for the measurement of active AM, so our values tend to be lower than Simon, T.P. et al [108]. Moreover, similar results were obtained in patients with UC in a phase 2 trial, namely the concentration of AM reached 5.9 to 7.4 times the basal values; day 1: 67.4 ± 16.0 and day 8: 84.7 ± 48.1 pg/mL [115].…”
Section: Phase 2a Clinical Trial For Covid-19mentioning
confidence: 56%
“…Progress of Clinical Trials Using AM AM was discovered in 1993, and the first human study was conducted in 1997 [107]. Early studies focused on the vasodilative effect of AM and used a relatively high dose to alter hemodynamics and humoral factors [108]. However, controlling the vasodilative effect of AM in general use is difficult; therefore, AM has not been adopted as a therapeutic agent for cardiovascular diseases [108].…”
Section: Clinical Trials Using Am For Covid-19mentioning
confidence: 99%
See 1 more Smart Citation
“…These results proved that ADM could be a useful marker to identify HF subjects at risk of rehospitalization due to suboptimal decongestion (34). Another study proposed that the stabilizing endothelial barrier effect, could be achieved by administrating 15 ng/kg/min of ADM, thus reducing pulmonary congestion without significant hemodynamic effects (36). Unfortunately, since ADM plasma levels are also very elevated in severe infections (especially in septic status), its use in HF patients must be carefully interpreted.…”
Section: Biomarkers Of Sympathetic Activationmentioning
confidence: 91%
“…Recently, an alternative pathway mediated by the PIEZO1adrenomedullin (ADM) axis was reported [ 51 ]. ADM is a circulatory vasodilator and diuretic and natriuretic peptide that is mainly produced by ECs [ 52 ]. Iring et al showed that PIEZO1 enhanced endothelial ADM secretion, then the secreted ADM bound to calcitonin receptor-like receptor (CALCRL) on ECs by an autocrine/paracrine fashion.…”
Section: Mouse Modelsmentioning
confidence: 99%